Analisis Efisiensi Pengeluaran Kesehatan Provinsi Maluku - Sihaloho, Estro Dariatno; Rijoly, Jacobus Cliff Diky; Siregar, Adiatma Yudistira Manogar (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
Maluku province is the province with the largest island in Indonesia. BPS Maluku report that Maluku province consists of 559 islands and divided into 9 regencies and 2 cities. Geographical conditions with many islands make the health care level not optimal in all districts in Maluku province. Health sector is one of the priorities programs of the government of Maluku Province. The government tries to increase the budget for health sector to increase the output of health sector in Maluku. This paper has two objectives. The first objective is to estimate scores of technical efficiency of health spending of regencies-cities in Maluku province. The second is to analyze the environmental factors that have an important role in enhancing the technical efficiency scores of regencies-cities in Maluku province. This study calculates scores of technical efficiency using Data Envelopment Analysis (DEA) method and use the Tobit method for the analysis of environmental factors. This study calculates the technical efficiency scores of health spending in 9 districts and 2 cities in Maluku province from 2012 to 2015. Key words: Efficiency, Health Spending, Data Envelopment Analysis, Tobit